Analisa Pengaruh Ketidakseimbangan Beban terhadap Efisiensi Listrik dalam Rangka Konservasi Energi di Gedung Rektorat UIN Suska Riau - Liliana Liliana (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
This research aim to know loss of active power generated by current at neutral line of transformator effect of laod imbalance in building of Rektorat UIN Suska Riau. Measurement of current, voltage, power factor and power were done in morning, evening and noon in order to be known how big current imbalance of phasa that happened so that have potency to improve current at neutral line of transformator. Ever greater of neutral current value hence active power losss ever greater. From Result of research known to three condition of measurement of losses of power biggest value energy effect of difference of current of phasa in the condition of daytime where moment of condition this there are difference of current of phasa which enough signifikan so that affect the increasing of current at neutral line with power losses was reaching 260.167 Watt.Keywords : Losses active power, load imbalance, phase current, neutral current, transformator.